Neighborhood-Level Socioeconomic Vulnerability and Perioperative Complications in Hysterectomy for Benign Indications - Bar-El, Liron; Barba, N Brandon; Shippey, Ernie; Garcia-Filion, Pamela; Kho, Rosanne M; Orlando, Megan S (Obstetrics and gynecology (New York. 1953), 2025)
To evaluate the association between neighborhood-level socioeconomic vulnerability, measured by the VVI (Vizient Vulnerability Index) and perioperative complications after hysterectomy for benign conditions. This retrospective cohort study analyzed patients who underwent hysterectomy for benign indications (2015-2024) using the Vizient Clinical Database. Patients were categorized into VVI quartiles (quartile 1, least vulnerable; quartile 4, most vulnerable) based on census tract data across nine socioeconomic domains: public safety, transportation, social cohesion, environmental quality, housing, neighborhood resources, health care access, education, and income. The primary outcome was the occurrence of perioperative complications, classified as major, minor, or any complication, with the Clavien-Dindo scale. Logistic regression was used to estimate the association between neighborhood vulnerability and surgical complications. Additional analyses evaluated the association of specific individual- and neighborhood-level social determinants, with race included as a marker of structural racism exposure, and perioperative outcomes. Among 1,055,338 patients, 18.4% (n=194,002) experienced complications, including 4.4% (n=46,356) major and 16.0% (n=169,361) minor complications. Complication rates increased proportionally across VVI quartiles ( P <.001). Major complications rose from 3.6% in quartile 1 to 5.7% in quartile 4; minor complications increased from 13.8% to 19.8%; and any complications increased from 15.9% to 22.5%. Higher VVI quartiles were associated with increased odds of major, minor, and any complications compared with quartile 1, with the strongest effects in quartile 4. After adjustment, the association remained significant for quartiles 3 and 4. Comorbidities were the strongest individual-level predictor. Black race, as a marker of structural racism exposure, was independently associated with complication risk across all VVI quartiles. We demonstrate that VVI, a measure of neighborhood-level social vulnerability, is associated with perioperative complications at the time of hysterectomy for benign indications independently of individual-level factors. Patients in the two most vulnerable quartiles experienced poorer outcomes compared with those in the least vulnerable quartile. Racial disparities, particularly affecting Black patients, persisted across VVI categories, reflecting the compounded influence of structural racism and neighborhood inequities.